2019
DOI: 10.14569/ijacsa.2019.0100676
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Multi Shippers Mechanism for Decentralized Cash on Delivery System

Abstract: One of the major problems of e-commerce globally is the selling and buying of goods among the parties over the Internet in which the traders may not trust their partners. Cash on delivery allows customers to pay in cash when the product is delivered to their home or a location they choose. This is sometimes called a payment system because customers receive goods before making a payment. This paper investigates a critical verification process issue in the cash on delivery system. In particular, we propose a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In the same year, Dasaklis presented a blockchain-enabled architecture and a proof-of-concept implementation of mobile operations [16]. In addition, Le et al [40,41] also exploit the advantages of blockchain technology to apply the cash-on-delivery model. Furthermore, in the process of delivery and receipt of goods between shippers, Ha Xuan Son et al developed a transport model based on a blockchain-based decentralized mechanism [42].…”
Section: Blockchain-based Management Systemsmentioning
confidence: 99%
“…In the same year, Dasaklis presented a blockchain-enabled architecture and a proof-of-concept implementation of mobile operations [16]. In addition, Le et al [40,41] also exploit the advantages of blockchain technology to apply the cash-on-delivery model. Furthermore, in the process of delivery and receipt of goods between shippers, Ha Xuan Son et al developed a transport model based on a blockchain-based decentralized mechanism [42].…”
Section: Blockchain-based Management Systemsmentioning
confidence: 99%
“…To prove the improvement of Blockchain for traditional shipping (i.e., Letter-of-Credit shipping (called LOC) or COD) Ha et al [6] described the current shipping system faced the massive drawback (e.g., dependence on trusted third parties, goods/order management, complicated payment processes among the parties in the same peer or ecosystem, losing the package and deposit for supplier and demander, respectively. To this end, Le et al [23] suggested that blockchain technology could fill these gaps via the usage of smart contracts and decentralized management in COD general and LOC special. For instance, the Ethereum ecosystem proposed a method called localEthereum which is introduced to support the transaction or DeFi Dapp between the suppliers and demanders [24].…”
Section: Related Workmentioning
confidence: 99%
“…To develop a larger scenario and increase the number of devices/users authorized quickly, other security issues such as security, privacy, availability for objects are still the challenges. For the security aspect, further works will be deployed in different scenarios like healthcare environment [25], [26], [27], cash on delivery [28], [29]. For the privacy aspect, we will exploit attribute-based access control (ABAC) [30], [31] to manage the authorization process of the SIP-MBA Platform via the dynamic policy approach [32], [33], [34].…”
Section: Future Workmentioning
confidence: 99%